"Stop. That's Wicked": Sexual Freedom in Brigid Brophy's The Burglar and Iris Murdoch's A Severed Head. (29th July 2017) - Osborn, Pamela
Abstract: This essay references letters sent to Brigid Brophy by Iris Murdoch and two of their most accomplished works, A Severed Head (1961), by Murdoch, and The Burglar (1968), a play by Brophy, to examine the conflict in their attitudes toward sexual freedom in the 1960s, which continues to have relevance in the twenty-first century. Murdoch's letters, which form part of the Iris Murdoch Collection in the Archives and Special Collections at Kingston University, reveal the logistical and emotional difficulties she and Brophy experienced in delineating their relationship, which was sporadically sexual, although both women were married and intermittently involved with other people. The complications of sexual freedom or nonmonogamy emerge in their work, particularly in A Severed Head and The Burglar, which can be read as part of the ongoing dialogue between the two writers. In her play, Brophy advocates an "enlightened morality" and an intellectual approach to promiscuity, while Murdoch's novel examines the primitive psychological responses that undermine the attempt to remain civilized when negotiating nonmonogamy, and she warns of the dangers of living by the mantra "all is permitted."